Implementing Combined Process (Mediation-Arbitration) in Industrial Relations Dispute Resolution: A Legal Justice Perspective - Roro Megabriella; Agus Mulya Karsona; Sherly Ayuna Putri (Eduvest - Journal of Universal Studies, 2025)
Combined Process (Mediation-Arbitration) is an innovative Alternative Dispute Resolution mechanism that unifies mediation’s flexibility and party autonomy with arbitration’s finality and enforceability. This hybrid offers a potentially more effective means of resolving Industrial Relations disputes. Although successfully applied in countries like China, Singapore, and the United States, Indonesia’s legal system lacks explicit provisions for this mechanism, creating uncertainty in its regulation and enforceability. This study aims to examine the use of the Combined Process (Mediation-Arbitration) for resolving industrial relations disputes and analyze it through the principle of legal justice. Using a normative juridical approach, the research reviews relevant laws and regulations to explore how this mechanism is implemented. Indonesia’s Law No. 2 of 2004 governs mediation and arbitration separately but does not explicitly acknowledge the Combined Process, leading to procedural ambiguity and unclear jurisdictional boundaries. This regulatory gap hinders the mechanism’s effective implementation despite its advantages in promoting efficiency and party satisfaction. The study finds that the Combined Process (Mediation-Arbitration) aligns with legal justice principles by fostering balance, transparency, and participation in dispute resolution. However, it requires formal legislative recognition and clear procedural rules to ensure legal certainty and practical effectiveness within Indonesia’s industrial relations framework.